2017
DOI: 10.1093/annonc/mdx250
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of local and metastatic recurrence in solitary fibrous tumor: construction of a risk calculator in a multicenter cohort from the French Sarcoma Group (FSG) database

Abstract: LRI and MRI rates increased between 10 and 20 years so relapses were delayed, suggesting that long-term monitoring is useful. This study also shows that different prognostic SFT sub-groups could benefit from different therapeutic strategies and that use of a survival calculator could become standard practice in SFTs to individualize treatment based on the clinical situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
121
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(168 citation statements)
references
References 21 publications
8
121
1
4
Order By: Relevance
“…This may reflect the difficulty in validating multitiered models in small cohorts with low‐frequency events. We also found that radiation therapy was not a prognostic factor for LR, in agreement with the findings of one recent study, but contradicting others; instead, the main risk factors for LR in our series were margin status and mitoses. Selection bias may limit interpretation of this analysis, as radiation was used on larger tumours (median 100 mm versus 53 mm, P = 0.0002), and data on radiation therapy were available only for a relatively small number of patients in our cohort.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This may reflect the difficulty in validating multitiered models in small cohorts with low‐frequency events. We also found that radiation therapy was not a prognostic factor for LR, in agreement with the findings of one recent study, but contradicting others; instead, the main risk factors for LR in our series were margin status and mitoses. Selection bias may limit interpretation of this analysis, as radiation was used on larger tumours (median 100 mm versus 53 mm, P = 0.0002), and data on radiation therapy were available only for a relatively small number of patients in our cohort.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, necrosis (together with haemorrhage) is also considered to be a risk factor in pleural risk models of SFT . The Salas models utilise tumour site in their models of SFT behaviour, showing that extremity tumours were at increased risk for metastasis, and visceral tumours were at increased risk for LR . However, another series found intra‐abdominal and retroperitoneal tumours to be associated with worse disease‐specific survival than tumours in other sites, and no correlation between site and distant metastasis, similar to our own findings .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We have proposed and validated a risk‐stratification model for SFT arising at all non‐meningeal sites based on a combination of tumour size, mitotic count, tumour necrosis and patient age . Other published risk prediction models include both site‐specific and more generally applicable models . However, none of these models address the underlying biology driving aggressive behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Solitary fibrous tumor (SFT) is a mesenchymal tumor with uncertain differentiation and intermediate malignant potential . SFTs can arise at any location (pleural or extrapleural) and display a wide histopathological spectrum, frequently with hemangiopericytoma‐like vessels . Several other histological patterns have also been described, including round cell, giant‐cell‐containing, epithelioid, myxoid, fat‐forming, pleomorphic and dedifferentiated variants .…”
Section: Introductionmentioning
confidence: 99%